Analisis Perawatan Mesin dengan Metode Reliability Centered Maintenance (RCM) terhadap Mesin Bag Inserter (FLEXIM) - Muchammad Firmansyah; Akhmad Wasiur Rizqi (G-Tech: Jurnal Teknologi Terapan, 2024)
PT. XYZ is a producer of margarine and shortening that faces challenges in maintaining the operational reliability of the FLEXIM bag inserter machine. This study aims to address these issues using three methods: Failure Mode and Effects Analysis (FMEA), Reliability Centered Maintenance (RCM), and Logic Tree Analysis (LTA). FMEA is used to identify critical components with the highest risk of failure, RCM to formulate optimal maintenance strategies, and LTA to analyze the cause-effect relationships of component failures within the system. The FMEA results show that the grippers and spoon components have the highest Risk Priority Numbers (RPN), 112 and 120 respectively. The resulting recommendations include increasing inspection frequency, preventive maintenance, and regular component replacement. Implementing these strategies is expected to reduce the risk of failure, improve machine reliability, and minimize operational downtime at PT. XYZ.